If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 2 = 3x + -12 Reorder the terms: 2 + -7x = 3x + -12 Reorder the terms: 2 + -7x = -12 + 3x Solving 2 + -7x = -12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + -7x + -3x = -12 + 3x + -3x Combine like terms: -7x + -3x = -10x 2 + -10x = -12 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + -10x = -12 + 0 2 + -10x = -12 Add '-2' to each side of the equation. 2 + -2 + -10x = -12 + -2 Combine like terms: 2 + -2 = 0 0 + -10x = -12 + -2 -10x = -12 + -2 Combine like terms: -12 + -2 = -14 -10x = -14 Divide each side by '-10'. x = 1.4 Simplifying x = 1.4
| 4u=36-5u | | 2x-5=2(3x-3) | | 8x+7y-4(8x-6y+5z)= | | 4x+x-8=2x-10 | | -3x-2=2x-8 | | X+(3y)i=4-9i | | Y=X-0.5(30-X) | | Y=300(3)y | | (2x-5)(5+3x-x^2)=0 | | 280=(2x+2)x | | 35x=149 | | 3x+6x-5=13 | | 6a^2-42a= | | 4ab^2-3a^2b+2ab-3a^2b= | | 18=-2X-12 | | 7a-62= | | 2(x^2-2x)+3x-4x^2= | | -2(z-5)-(6z-9)=-9z | | 2x-(-3)=-5x-(17) | | j+4j=15 | | 560=0.11x+0.03x | | 0.20=log(y) | | 3(5p+2)-4= | | 123k+1000q-2987=2098765 | | -7p+15=-5p+5 | | 2x-2(5x+3)=12(x-3)+17 | | 18+4m=-7(7m+5) | | 6x+12=18-4x | | 10m+15=55 | | 3x^2y-5x+3y-3x^2y= | | 8(r-7)=-8r+24 | | 16+7x+-5+x=11x+-3+-2x |